Prognostic value of post-treatment ¹⁸F-fluorodeoxyglucose positron emission tomography in uterine cervical cancer patients treated with radiotherapy: a systematic review and meta-analysis - Kim, Yeon Joo; Han, Sangwon; Kim, Young Seok; Nam, Joo Hyun (Journal of gynecologic oncology, 2019)
To perform a systematic review and meta-analysis of the prognostic value of post-treatment ¹⁸F-fluorodeoxyglucose positron emission tomography (¹⁸F-FDG PET) in uterine cervical cancer patients treated with radiotherapy (RT) with or without chemotherapy. PubMed and Embase databases were searched up to July 22, 2018, for studies which evaluated the response outcomes of ¹⁸F-FDG PET following RT, and their prognostic significance in uterine cervical cancer was assessed with overall survival (OS) or progression-free survival (PFS) as endpoints. Hazard ratios (HRs) were meta-analytically pooled using the random-effects model. Eleven studies with 12 patient cohorts including 1,104 patients were included. For a quantitative synthesis of OS, 7 cohorts were included. Two cohorts which reported disease-specific survival instead of OS were also included with flexibility. Pooled HR of complete metabolic response (CMR) compared to partial metabolic response (PMR) was 0.19 (95% confidence interval [CI]=0.11-0.31). Pooled HR of CMR compared to progressive metabolic disease (PMD) was more evident at 0.07 (95% CI=0.04-0.12), and that of CMR compared to both PMR and PMD was 0.20 (95% CI=0.12-0.34). Quantitative synthesis for PFS was performed with a total of 8 cohorts. Pooled HR of CMR was 0.17 (95% CI=0.10-0.29) compared to PMR, 0.02 (95% CI=0.01-0.06) compared to PMD and 0.12 (95% CI=0.07-0.19) compared to both PMR and PMD. Response results of post-RT ¹⁸F-FDG PET were significant prognostic factors in patients with uterine cervical cancer, and ¹⁸F-FDG PET could be a reasonable follow-up imaging modality.